Non-Apophantic Logos as Model Ontology - Matiashvili, Lasha (European Scientific Journal, ESJ, 2017)
In recent years Giorgio Agamben within his “Homo Sacer” project has elaborated the theory of “two ontologies”, in which his challenging and crucial assumption was the juxtaposition of the ontology of ἐστi (to be or is) to the ontology of ἔστω (ought). At first glance, this central claim of Agamben can be seen as innocent and neutral for any kind of philosophical discourse. However, His archeological investigation of the concepts of duty and commandment turns out to be the mere preliminary stage for his explosive hypothesis, according to which ontological machine and entire philosophical tradition of the west oppressed and ignored the so called modal ontology of commandment. The main aim of this article is to ascertain the meaning, field and function of non-apophanitic discourse, which can be placed beyond propositional truth and falsity. We are going to analyze three forms of non-apophantic discourse, namely, prayer, commandment and oath which according to their essence, is linked to the modal ontology. Another purpose is to demonstrate that in modern structurally differentiated and secularized societies, non-apophantic logos is a concealed form and source of power.